On Pronunciation in a Multilingual Dictionary: The Case of Lukumi, Olukumi and Yoruba Dictionary - Uguru, Joy O.; Okeke, Chukwuma O. (Lexikos, 2020)
This study centres on reflecting the pronunciation of lemmas in a proposed multilingual dictionary of Lukumi, Olukumi and Yoruba. It shows how the differences and similarities in their pronunciation can be displayed in the proposed dictionary. Lukumi is spoken in Cuba while Olukumi and Yoruba are spoken in Nigeria. The parent language, Yoruba, was used as a reference point to highlight the etymology of Lukumi and Olukumi as well as to buttress their similarities. Two downloaded Lukumi wordlists making up 134 words were used to elicit information on Olukumi equivalents through oral interview. Twenty-two words are used as sample entries. Following Mashamaite's method of promoting the compilation of bilingual dictionaries between African languages, the study presents Lukumi as the source language while Olukumi and Yoruba are the target languages; English translations of the lemmas are shown. The pronunciation of the lemmas is given alongside their meanings and grammatical categories. No dictionary of any Nigerian language has pronunciation of headwords given; hence this study is a positive innovation; also, the display of pronunciation provides evidence of the similarities shared by the three languages. The transcription of the lemmas serves as a good learning aid for the language learners. The dictionary will go a long way to preserve the endangered Lukumi and Olukumi languages.